2011
DOI: 10.1002/marc.201100292
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of Crystalline Polyaniline on Reduced Graphene Oxide

Abstract: Due to its unique electronic properties, graphene has already been identified as a promising material for future carbon based electronics. To develop graphene technology, the fabrication of a high quality P-N junction is a great challenge. Here, we describe a general technique to grow single crystalline polyaniline (PANI) films on graphene sheets using in situ polymerization via the oxidation-reduction of aniline monomer and graphene oxide, respectively, to fabricate a high quality P-N junction, which shows di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…[10][11][12] It has been reported that both nanotubes and graphene accelerate polymer crystallization when they have strong interactions with polymers. [13][14][15][16][17] The resulting interfacial crystals possess different microstructures and morphologies as compared to those in the bulk in terms of polymer chain orientation and crystal polymorphism. Importantly, the ordered interfacial microstructures significantly improve the interfacial adhesion and load transfer.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] It has been reported that both nanotubes and graphene accelerate polymer crystallization when they have strong interactions with polymers. [13][14][15][16][17] The resulting interfacial crystals possess different microstructures and morphologies as compared to those in the bulk in terms of polymer chain orientation and crystal polymorphism. Importantly, the ordered interfacial microstructures significantly improve the interfacial adhesion and load transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The crystalline PANI peaks in EBP‐PANI are induced, since the epoxide groups in EBP may be involved in PANI formation as oxidants. In this regard, according to the paper published by Majumdar et al ., anilinium ions can be arranged along the epoxide group arrays, in a head‐to‐tail fashion, with their benzene rings perpendicular to the surface of the graphene oxide. Then, the portion of epoxide rings can be strained and uniformly disassembled.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike previous reported method to attach epoxide functional groups via a zwitterionic method, the carbon nanotubes were functionalized by acid treatment (meta‐chloroperoxybenzoic acid [m‐CPBA]) to directly introduce epoxide functional groups on their surfaces. The electrochemical performances of the hybrid supercapacitor prepared in this article were analyzed, based on the three following hypotheses: (1) epoxide groups on functionalized carbon nanotubes will act as oxidants when aniline is polymerized, resulting in crystalline PANI exhibiting high conductivity; (2) hydrogen bonds can be formed between epoxide groups on the functionalized carbon nanotubes and amine in PANI, leading to improved binding forces in the composite; and (3) chemical interactions arise between AgNPs and nitrogen atoms in PANI, which provide high conductivity and improve the specific capacitance . All these factors can lead to a device with improved electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…4. The diffractogram of PANI exhibits a semi-crystalline peak at 26° which is the major distinctive peak of PANI [22]. The broad peak of PANI is superimposed by the diffraction peak of Gr and a highly pronounced peak of PANI doped Gr is observed at 27° in the 15 wt% composite diffractogram whose height increases proportionally to the weight percentage of Gr in the polymer matrix.…”
Section: Xrd Analysismentioning
confidence: 97%